Unique Phenotypes of Heart Resident Type 2 Innate Lymphoid Cells - Deng, Yafei; Wu, Shuting; Yang, Yao; Meng, Meng; Chen, Xin; Chen, Sha; Li, Liping; Gao, Yuan; Cai, Yue; Imani, Saber; Chen, Bingbo; Li, Shuhui; et al. (Frontiers in Immunology, 2020)
Innate lymphoid cells (ILCs), including ILC1s, ILC2s, and ILC3s, play critical roles in regulating immunity, inflammation, and tissue homeostasis. However, limited attention is focused on the unique phenotype of ILCs in the heart tissue. In this study, we analyzed the ILC subsets in the heart by flow cytometry and found that ILC2s were the dominant population of ILCs, while a lower proportion of type 1 ILCs (including ILC1 and NK cells) and merely no ILC3s in the heart tissue of mice. Our results show that ILC2 development kinetically peaked in heart ILC2s at the age of 4 weeks after birth and later than lung ILC2s. By conducting parabiosis experiment, we show that heart ILC2s are tissue resident cells and minimally replaced by circulating cells. Notably, heart ILC2s have unique phenotypes, such as lower expression of ICOS, CD25 (IL-2Rα), and Ki-67, higher expression of Sca-1 and GATA3, and stronger ability to produce IL-4 and IL-13. In doxorubicin-induced myocardial necroptosis model of mouse heart tissue, IL-33 mRNA expression level and ILC2s were remarkably increased. In addition, IL-4 production by heart ILC2s, but not lung ILC2s, was also dramatically increased after doxorubicin treatment. Our results demonstrate that heart-resident ILC2s showed tissue-specific phenotypes and rapidly responded to heart injury. Thus, further studies are warranted to explore the potential for IL-33-elicited ILC2s response as therapeutics for attenuating heart damage.